“BENEFITS AND DANGERS OF TECHNOLOGY” (Ustozlar uchun, 2025)
This article explores the multifaceted impacts of technology on modern society, focusing on both its benefits and potential dangers. Technology has revolutionized various aspects of human life, including communication, education, healthcare, industry, and entertainment. The article highlights how technological advancements improve productivity, enhance access to information, promote innovation, and facilitate global connectivity. In education, technology has transformed teaching and learning processes, providing interactive platforms, online resources, and distance learning opportunities. In healthcare, technological innovations have improved diagnostics, treatment, and patient monitoring, contributing to longer life expectancy and better quality of life.